VALUASI LINGKUNGAN DALAM PENENTUAN POTENSI EKONOMI OBJEK MIKROWISATA DESA TANGGERAN, TONJONG, BREBES, JAWA TENGAH - Safitra, Dhian Adhetiya; Suheri, Asep (LPPM Universitas Terbuka, 2023)
The pandemic causes the need for new jobs. Most workers from rural areas experienced many layoffs due to the significant reduction in employment opportunities. One of the jobs that can be an option to accommodate these workers is the tourism sector. With community-based tourism, local workers can be absorbed by areas with natural tourism potential. The challenge faced by prospective tourist objects is how significant the potential of the tourism object is and how much the tariff will be set. This study aims to find the economic potential of the object of research used by the micro tourism manager in determining the rates or price ranges used in the sale of culinary or other goods/services. This study uses environmental valuation with the Travel Cost Method to calculate several potential economic objects to be used as the basis for investors to invest in research objects. In addition, managers can also use the average willingness to pay (WTP) as the basis for entrance fees, parking, and culinary prices offered. Considering visitors' preferences is a tourist attraction that looks free; the WTP value for the entrance fee is IDR 0. This study concludes that without managing micro-tourism objects, the value is IDR 63.129.290.00 to IDR71.835.382,00, while if it is managed, the potential increases to IDR5.752.023.104,00. The recommended culinary price is no more than IDR12.084,00, while the parking fee can be collected at IDR 1.000,00.